Penerapan Metode Pembelajaran Contextual Teaching And Learning dalam Meningkatkan Hasil Belajar Siswa Kelas IV SDN 107401 Pematang Lalang - Harry Dianto; Nuri Ramadhan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study aims to improve the learning outcomes of fourth-grade students at SDN 107401 Pematang Lalang through the application of the Contextual Teaching and Learning (CTL) method. The research employed a classroom action research (CAR) design conducted over two cycles. Data were collected through learning outcome tests, interviews, field notes, and documentation, and were analyzed using quantitative descriptive statistics and qualitative analysis techniques. The results showed that before the implementation of CTL, the percentage of students achieving learning mastery was only 21.4% (3 students). After the implementation of CTL in Cycle I, this percentage increased to 42.8% (6 students), and in Cycle II, it further increased to 85.71% (12 students). These findings indicate that the CTL method is effective in improving students' learning outcomes in Social Studies on the topic of production technology, communication, and transportation in the past and present.